Leading digital : turning technology into business transformation - Westerman, George, 1963-; Bonnet, Didier; McAfee, Andrew (Boston : Harvard Business Review Press, 2014)
"Leading Digital makes the provocative argument that the next imminent phase of digital technology adoption - driven by the convergence of mobility, analytics, social media, cloud computing, and embedded devices - will make everything that's happened so far look like a prelude. The authors, a trio of highly regarded thought leaders on corporate digital transformation, say changes in the digital realm so far have focused on high tech and media companies - but there's still a whopping 94% of the business economy that needs to change. This book will show them how. George Westerman of MIT, Didier Bonnet of Capgemini Consulting, and Andrew McAfee, also at MIT, say there is opportunity for these businesses to learn from those that have already mastered the digital landscape. Based on a study of more than 400 large, mainstream firms in every industry around the globe, the authors usefully break down how these organizations have used their own digital transformation to gain strategic, competitive advantage. Readers will learn how these digital leaders have transformed their businesses through smart and rigorous digital investments, and through smart and effective leadership of the change. Leading Digital offers practical, real-life tested frameworks that can be instantly applied. Case studies include Nike, Caesars, Burberry, Asian Paints, Pages Jaunes, Codelco, and more"--
What is digital mastery? -- Creating a compelling customer experience -- Exploiting the power of core operations -- Reinventing business models -- Crafting your digital vision -- Engaging the organization at scale -- Governing the transformation -- Building technology leadership capabilities -- Framing the digital challenge -- Focusing investment -- Mobilizing the organization -- Sustaining the digital transformation.
Includes bibliographical references and index.
Print version record.
Keywords: Information technology -- Management; Strategic planning; Organizational change; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books